Modification of Natural Proanthocyanidin Oligomers and Polymers Via Chemical Oxidation under Alkaline Conditions - Bin Imran Iqbal; Karonen Maarit; Salminen Juha-Pekka; Engström Marica T (American Chemical Society, 2022)
We tested the susceptibility of 102 proanthocyanidin (PA)-rich plant extracts to oxidation under alkaline conditions and the possibility to produce chemically modified PAs via oxidation. Both the nonoxidized and the oxidized extracts were analyzed using group-specific ultrahigh-performance liquid chromatography−diode array detection−tandem mass spectrometry (UHPLC−DAD−MS/MS) methods capable of detecting procyanidin (PC) and prodelphinidin (PD) moieties along the two-dimensional (2D) chromatographic fingerprints of plant PAs. The results indicated different reactivities for PCs and PDs. When detected by UHPLC−DAD only, most of the PC-rich samples exhibited only a subtle change in their PA content, but the UHPLC−MS/MS quantitation showed that the decrease in the PC content varied by 0−100%. The main reaction route was concluded to be intramolecular. The PD-rich and galloylated PAs showed a different pattern with high reductions in the original PA content by both ultraviolet (UV) and MS/MS quantitation, accompanied by the shifted retention times of the chromatographic PA humps. In these samples, both intraand intermolecular reactions were indicated.